Reliability and relevance of fair values: Private equity investments and investee fundamentals - Petrus Ferreira; Roman Kräussl; Wayne R. Landsman; Maria Nykyforovych; Peter F. Pope (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
We directly test the reliability and relevance of fair values reported by listed private equity firms (LPEs), where the unit of account for fair value measurement attribute (FVM) is an investment stake in an individual investee company. FVMs are observable for multiple investment stakes, fair values are economically important, and granular data on investee economic fundamentals that should underpin fair values are available in public disclosures. We find that LPE fund managers determine valuations based on accounting-based fundamentals - equity book value and net income - that are in line with those investors derive for listed companies. Additionally, our findings suggest that LPE fund managers apply a lower valuation weight to investee net income if direct market inputs are unobservable during investment value estimation. We interpret these findings as evidence that LPE fund managers do not appear mechanically to apply market valuation weights for publicly traded investees when determining valuations of non-listed. We also document that the judgments that LPE fund managers apply when determining investee valuations appear to be perceived as reliable by their investors.
urn:nbn:de:hebis:30:3-469338
Keywords: 330